How a local brand can compete against international giants - Vardar, Nükhet (Henry Stewart Talks, 2018)
Rise of Jollibee in the Philippines, Tony Tan’s personality and management style, Branding and targeting in Jollibee, Internationalization Strategy of Jollibee, International market entry strategies